Peru : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper for Peru shows that during the years of strong growth and high commodity prices, the Peruvian authorities have conducted a prudent fiscal policy, maintaining a broadly neutral fiscal stance. During 2004-08, while the revenue-to-GDP ratio increased 3.7 percentage points, the expenditure ratio rose only 0.9 percentage points. Expenditure control focused on current spending and coincided with increasing government investment aimed at enhancing public access to infrastructure and social services. Fiscal policy has also outperformed budgets approved by congress, owing to higher-than-anticipated revenue, as well as the need to limit inflation pressures.